Rat strain response differences upon exposure to technical or alpha hexabromocyclododecane. (August 2019) - Gannon, A.M.; Nunnikhoven, A.; Liston, V.; Rawn, D.F.K.; Pantazopoulos, P.; Fine, J.H.; Caldwell, D.; Bondy, G.S.; Curran, I.H.A.
Abstract: Hexabromocyclododecane (HBCD) is a brominated flame retardant which was recommended by a UN expert body under the Stockholm Convention to be eliminated from the global marketplace in 2011; however, due to its ability to persist in the environment, undergo long-range transport and bioaccumulate, it remains a concern for human health. The commercial mix of HBCD (T-HBCD) consists of α-HBCD, β-HBCD and γ-HBCD. Although the γ-HBCD (79%) isomer is the predominant isomer of T-HBCD, the most bioaccumulative isomer detected in mammals is the α-HBCD isomer. This study was undertaken to investigate three rat strains treated with commercial grade (technical) HBCD or HBCD enriched with the α isomer (A-HBCD) and to examine strain- and sex-related differences in response to exposure. Female Sprague Dawley (SD), Wistar (WI) and Fischer F344 (FI) rats were exposed for 28 days to either T-HBCD or A-HBCD in feed, at doses of 0, 250, 1250 and 5000 mg/kg diet. The FI rodent strain was found to be the most sensitive to effects of HBCD based on the greatest number of significantly affected endpoints which indicated that T-HBCD primarily affected liver and thyroid, resulting in multiple health effects. Consequently, male FI were included in the study and exposed to T- and A-HBCD. Histopathological data supports previously reported effects of HBCD on the thyroid and endocrine system although the effects in FI rats are significantly elevated compared to other strains. As with T-HBCD, liver and thyroid were found to be target organs of A-HBCD. Sex differences, specifically in tissue concentration levels, immune response parameters and in number and severity of thyroid and liver lesions, following exposure to either T- or A-HBCD were apparent, with treatment eliciting a greater response in males. Residue analysis revealed that α-HBCD is more bioaccumulative than γ-HBCD in all rodent strains, with levels of HBCD in animals treated with A-HBCD several fold higher for all tissues tested (7–11 fold at the highest dose). Thus, residue data supports the selective uptake (implies there are differences in bioavailability and/or bioaccumulation; is this the case or do certain isomers simply have a longer half-life) of specific isomers, with α-HBCD > γ-HBCD. Taken together, our study highlights the importance of selecting the most appropriate strain and of including both sexes in studies to ensure that sex-related differences in response to test chemical is taken into consideration. Moreover, ours is the first study to show the effects of a sub-acute exposure to a diet containing only HBCD enriched for the α isomer, which better represents the isomer ratios present in the biota due to bioaccumulation. Highlights: The α isomer of HBCD in tissues from A-HBCD diets accumulated at levels 4–12 times compared to tissues from T-HBCD. Study highlights the sex-related differences to chemical exposure and reinforces the need for comparative studies. Strains differences effect response to a chemical exposure, highlighting importance of appropriate animal model. Histopathology found significant effects of HBCD on rat thyroid and BMD's lower than those for rat liver.